Partisipasi Masyarakat Dalam Pengelolaan Destinasi Wisata Halal Kawasan Mandeh Sumatra Barat - Muhammad Akbar Rezkim; Windy Anatasya; Putri Aprilliany; Ade Saputra Hendri; Marta Widian Sari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research aims to assess community participation in managing halal tourist destinations in the Mandeh area, Pesisir Selatan, West Sumatra. Mandeh Island, a tourist destination located in Pesisir Selatan Regency, West Sumatra, Indonesia, has long been a tourist destination that attracts the attention of tourists from both within and outside the country. Its stunning natural charm, white sandy beaches and rich marine ecosystem make Mandeh Island one of the potential tourist areas in Indonesia. Additionally, Indonesia has a large Muslim population, and Muslim-Friendly Tourism is gaining increasing attention in the global tourism industry.